=
Note: Conversion is based on the latest values and formulas.
How do you integrate #sqrt(1-x^2)#? - Socratic 29 Mar 2018 · How do you integrate #sqrt(1-x^2)#? Calculus Techniques of Integration Integration by Substitution. 1 ...
How do you differentiate #y=ln(e^x+sqrt(1+e^(2x)))#? - Socratic 9 Aug 2016 · Calculus Differentiating Exponential Functions Differentiating Exponential Functions with Base e. 1 Answer . Euan S.
How do you simplify \sqrt { ( 1- \cos \theta ) ( 1+ \cos ... - Socratic 20 May 2018 · #\sqrt{(1-cos theta)(1+ cos theta)} = sqrt{1 - cos^2 theta}=sqrt{sin^2 theta} = |sin theta| # That's because the radical sign applied to a real number refers to the principal square root which is the positive square root, thus the absolute value is correct. But Lucy's answer is really the one that arises in practice.
How do you integrate #sqrt(4x² + 1)#? - Socratic 14 Aug 2018 · #color(white)(int \ sqrt(4x^2+1) \ dx) = 1/4u + 1/4 sinh u cosh u + C# #color(white)(int \ sqrt(4x^2+1) \ dx) = 1/4 sinh^(-1) x + 1/2x sqrt(4x^2+1) + C# Answer link
Simplify #sqrt((1+cosx)/(1-cosx))# - Socratic 10 Jun 2017 · cscx+cotx sqrt((1+cosx)/(1-cosx)) =sqrt((1+cosx)^2/(1-cos^2x)) =sqrt((1+cosx)^2/(sinx)^2) =(1+cosx)/sinx =cscx+cotx
How do you simplify #sqrt(1+tan^2x)#? - Socratic 13 Jan 2017 · Using: #cos^2 x + sin^2 x = 1# #tan x = sin x / cos x# #sec x = 1/cos x# we find: #sqrt(1+tan^2 x) = sqrt(1+(sin^2 x)/(cos^2 x))#
How to you find the general solution of sqrt(1-4x^2)y'=x? - Socratic 8 Nov 2016 · y = -1/4 sqrt(1-4x^2) + C Changing the notation from Lagrange's notation to Leibniz's notation we have: sqrt(1-4x^2)dy/dx = x which is a First Order separable DE which we can rearrange as follows: dy = x/sqrt(1-4x^2) dx => int dy = int x/sqrt(1-4x^2) dx To integrate the RHS we need to use a substitution Let u=1-4x^2 => (du)/dx = -8x => -1/8du = xdx Se we can now …
What is the Maclaurin series for? : sqrt(1-x) - Socratic 23 Aug 2017 · f(x) = 1 - 1/2x - 1/8x^2 - 1/16x^3 - 5/128x^4 + ... Let: f(x) = sqrt(1-x) We seek a Taylor Series, as no pivot is supplied, it is assumed that an expansion about the pivot x=0 is required. This is known as a Maclaurin series and is given by f(x) = f(0) + (f'(0))/(1!)x + (f''(0))/(2!)x^2 + (f'''(0))/(3!)x^3 + ... (f^((n))(0))/(n!)x^n + ... Although we could use this method, …
What is the square root of negative one? + Example - Socratic 20 Sep 2015 · The principal square root of minus one is i. It has another square root -i. I really dislike the expression "the square root of minus one". Like all non-zero numbers, -1 has two square roots, which we call i and -i. If x is a Real number then x^2 >= 0, so we need to look beyond the Real numbers to find a square root of -1. Complex numbers can be thought of as …
How do you use the binomial series to expand #f(x)= sqrt(1+x 25 Nov 2016 · How do you use the binomial series to expand #f(x)= sqrt(1+x^2)#? Precalculus The Binomial Theorem The Binomial Theorem. 1 Answer